The amphibians and reptiles of Manu National Park and its buffer zone, Amazon basin and eastern slopes of the Andes, Peru - Catenazzi, Alessandro; Lehr, Edgar; May, Rudolf von (Biota Neotropica, 2013)
We compile a list of all amphibians and reptiles known to occur within Manu National Park, Peru and its buffer zone, located in one of the world's biodiversity hotspots. Covering approximately 0.01% of the planet's terrestrial surface, this protected area preserves 155 species of amphibians and 132 species of reptiles, corresponding to 2.2% and 1.5% respectively of the known diversity for these groups. Moreover, Manu National Park preserves natural habitats and populations of one critically endangered (Atelopus erythropus), three endangered (Bryophryne cophites, Pristimantis cosnipatae and Psychrophrynella usurpator), three vulnerable amphibians (Atelopus tricolor, Gastrotheca excubitor, Rhinella manu) and two vulnerable reptiles (Chelonoidis denticulata, Podocnemis unifilis), according to the threat categories of the IUCN Red List.